2017
DOI: 10.1016/j.fertnstert.2017.07.419
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-reduction potential: a new marker of oxidative stress and sperm quality

Abstract: men, but these results were not statistically significant. The pooled effect estimates were not materially affected by the test method (SCSA or TUNEL or study population (general population vs. infertile men). Heterogeneity was high across all comparisons, suggesting a marked variation across the included studies.CONCLUSIONS: Overweight and obesity conditions have minimal effects on sperm DNA fragmentation in men in reproductive age. The clinical implications of the association between BMI and sperm DNA fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Due to enhancement of oxygen consumption during exercise, reactive oxygen species (ROS) are excessively generated and affect testicular normal structure and function. 7,11,24 Testis is a susceptible tissue to the oxidative stress because of the high level of cell division and existence of high level of unsaturated fatty acids. 26 Also, during extensive exercise, the blood supply of testis decreases and subsequently testosterone secretion declines and hypoxia in testis leads to apoptosis of germ cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to enhancement of oxygen consumption during exercise, reactive oxygen species (ROS) are excessively generated and affect testicular normal structure and function. 7,11,24 Testis is a susceptible tissue to the oxidative stress because of the high level of cell division and existence of high level of unsaturated fatty acids. 26 Also, during extensive exercise, the blood supply of testis decreases and subsequently testosterone secretion declines and hypoxia in testis leads to apoptosis of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…27 There are several research studies both in animals and humans which have demonstrated that intensive exercise leads to the reduction of sperm quality parameters and production of reproductive hormone, and to the increase in the oxidative stress and lipid peroxidation. 7,8,11,18,28,29 Intensive exercise induces oxidative stress in testis tissue via decreasing the anti-oxidative enzymes (superoxide dismutase and glutathione peroxidase) and increasing oxidative enzyme (malondialdehyde). 30 Swimming exercise is one of the best studied animal models of intensive forced exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations